Nonradical activation of peroxydisulfate over Fe/N doped mesoporous carbon for selective removal of organic pollutant. Issue 2 (April 2023) - Liu, Zhuoyue; Wang, Ke; Li, Danyang; Wang, Zhenxin; Yang, Shengjiong; Pang, Heliang; Wang, Gen; Ding, Dahu; Miao, Delu
Abstract: Mesoporous carbon materials are promising catalysts for peroxydisulfate (PDS) activation for degrading aqueous organic pollutants but limited by the intrinsic inertness. Herein, co-doping of iron and nitrogen into the mesoporous carbon framework was performed via thermal conversion of metal-polyphenol coordination polymers (Fe-TA) to synthesize Fe/N co-doped mesoporous carbon for efficient PDS activation. Owing to the large surface area, high graphitization degree and defective configurations, the Fe/N co-doped mesoporous carbon (Fe/N-MCs) exhibited superior catalytic performance toward the degradation of organic pollutants. Electron paramagnetic resonance tests, chemical quenching experiments, electrochemical analysis and spectra measurements revealed that the degradation of organic pollutants over the Fe/N-MCs followed a nonradical oxidation pathway based on electron transfer process. Graphite nitrogen and hydroxyl (C-OH) groups on the defective edges of Fe/N-MCs were proved to be possible active sites for PDS activation. PDS catalyzed by the Fe/N-MCs exhibited strong anti-interference capability to surrounding inorganic ions (such as Cl –, CO3 2–, NO3 – and SO4 2– ) and natural organic matters, making it a promising candidate for the degradation of organic pollutants. This work provides a new prospect for developing highly active mesoporous carbon materials via heteroatom doping for PDS activation for wastewater decontamination. Graphical Abstract: The degradation of organics over Fe/N co-doped mesoporous carbon followed a nonradical oxidation pathway based on electron transfer regime. Graphite nitrogen and hydroxyl (C-OH) groups on the defective edges of carbon layer were proved to be possible active sites for PDS activation. ga1 Highlights: Fe/N doped mesoporous carbon was prepared and employed as a PDS activator. Co-doping of Fe and N enabled high graphitization degree and defective configurations. Organics removal followed a nonradical pathway based on electron transfer process. Fe/N doped mesoporous carbon maintained high activity in complicated water matrix.